Optimal Restrictions on Foreign Trade and Investment: Note - Batra, Raveendra N. (American Economic Review, 2016)
Optimal policv in the presence of international trade and investment, which has been previouslIN analyzed by Murray Kemp and Ronald Jones (1967) in the context of a twofactor, two-good general equiilibrium model, constitutes the subject of analysis in a recent article in this Review byT Franz Gehrels. Gehrels' framework, which postulates a three-factor, two-good economy, differs from that of Kemp and Jones in format but not in substance. Nevertheless, Gehrels has made an important contribution by providing a more complete discussion of partial optimization and by deriving optimal tariffs and taxes in the presence of the interindustrv wage differential that characterizes factor markets in the underdeveloped countries. The objective of this note is to show that Gehrels' optimal policy in the presence of the wage differential is incomplete and that his modification of the optimum tariff formula is not always valid. The assumptions and notations used in this note are the same as those introduced bv Gehrels. The problem is to maximize the social utilitv function